2012
DOI: 10.1186/1471-2474-13-62
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study to evaluate the clinical and cost-effectiveness of a self-managed exercise programme versus usual physiotherapy for chronic rotator cuff disorders: protocol for the SELF study

Abstract: BackgroundShoulder pain is the third most common reason for consultation with a physiotherapist and up to 26% of the general population might be expected to experience an episode at any one time. Disorders of the shoulder muscles and tendons (rotator cuff) are thought to be the commonest cause of this pain. The long-term outcome is frequently poor despite treatment. This means that many patients are exposed to more invasive treatment, e.g. surgery, and/or long-term pain and disability.Patients with this disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…The protocol was approved by the National Research Ethics Service Committee Yorkshire & the Humber (Ref 11/YH/0443) and published online (6).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was approved by the National Research Ethics Service Committee Yorkshire & the Humber (Ref 11/YH/0443) and published online (6).…”
Section: Methodsmentioning
confidence: 99%
“…Once treated by an orthopedic rehabilitation specialist (including physiotherapist), high levels of patient satisfaction (99.5%) and better outcomes were achieved [3]. Physiotherapy has proved to produce persistent benefits in many chronic and disabling conditions like knee pain [4], low back pain [5], neck pain [6] and shoulder pain [7]. Jessep et al in 2009 [4] conducted a study on 64 patients diagnosed with chronic knee pain attending the outpatient Physiotherapy department in UK.…”
Section: Discussionmentioning
confidence: 99%
“…This trial threw light on the positive benefits that Physiotherapy treatment may have for chronic neck pain. The study by Littlewood et al in 2012 [7] looked into the benefits of Physiotherapy over self-managed exercises for patients suffering from disabling shoulder pain. In another study by Pinnington et al in 2004 [11], it was found that early intervention by a physiotherapist is feasible and acceptable to the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One barrier to performing tendon-loading studies is the belief that tendon rehabilitation is not a ‘one size fits all’ and is not conducive to single intervention RCTs preferred by academics or clinical journals. However, a study using a pragmatic approach and general principles has been implemented for rotator cuff tendon pathology,9 so there is no reason why we cannot extrapolate this approach to other tendinopathies. …”
mentioning
confidence: 99%